Lignocellulosic fibers and wood handbook : renewable materials for today's environment - Pizzi, Antonio; Belgacem, Mohamed Naceur; Pizzi, A. (Antonio), 1946- (Hoboken, New Jersey : John Wiley & Sons, 2016)
This book will focus on lignocellulosic fibres as a raw material for several applications. It will start with wood chemistry and morphology. Then, some fibre isolation processes will be given, before moving to composites, panel and paper manufacturing, characterization and aging.
Includes bibliographical references and index.
Print version record.
Keywords: Lignocellulose; Renewable natural resources; BUSINESS & ECONOMICS -- Real Estate -- General; Lignocellulose; Renewable natural resources; Electronic books